2021
DOI: 10.1017/wet.2021.76
|View full text |Cite
|
Sign up to set email alerts
|

Performance of tank-mix partners with isoxaflutole across the Cotton Belt

Abstract: BASF Corporation has developed P-hydroxyphenylpyruvate dioxygenase (HPPD) inhibitor-resistant cotton and soybean that will allow growers to use isoxaflutole in future weed management programs. In 2019 and 2020, a multi-state research project was conducted non-crop to examine weed control following isoxaflutole applied preemergence alone and with a number of tank mix partners at high and low labeled rates. At 28 DAT, Palmer amaranth was controlled ≥95% at 6 of 7 locations with isoxaflutole plus the high rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…It is important to note, like 2019, IFT alone caused 0% cotton injury 9 to 14 DA PRE. Cotton injury observed in this study is similar to that observed by Cahoon et al (2015a) and Foster (2021). Previous research carried out in North Carolina found that cotton was injured ≤3% 18 to 27 DA PRE by acetochlor, diuron, fomesafen, and fluometuron and two- and three-way combinations of the residual herbicides (Cahoon et al 2015a).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…It is important to note, like 2019, IFT alone caused 0% cotton injury 9 to 14 DA PRE. Cotton injury observed in this study is similar to that observed by Cahoon et al (2015a) and Foster (2021). Previous research carried out in North Carolina found that cotton was injured ≤3% 18 to 27 DA PRE by acetochlor, diuron, fomesafen, and fluometuron and two- and three-way combinations of the residual herbicides (Cahoon et al 2015a).…”
Section: Resultssupporting
confidence: 92%
“…IFT, applied alone or in combination with other herbicides, caused minimal cotton injury, thus demonstrating potential for safe use at either timing. These findings are further reinforced by research conducted in Arkansas and Texas, which also reported no decrease in cotton stand, minimal injury, and no reductions in lint yield from IFT applied PRE or EPOST when used alone or combined with other herbicides (Fleming et al 2021; Foster 2021). Additionally, the experimental cotton cultivar demonstrated tolerance to commonly used cotton herbicides PRE and POST.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations